Zine-cidade: vivendo a cidade através da criação de zines - Malveira, Ícaro Lênin Maia (2020)
The present research has its essence in the composition of a zine-city. Througout the path crossed, my activities as a teacher and ziner come together, as well as the trajectory traves in the Masters of Arts at UFC and, finally, the formation and performance of the Creation and Arts Group, a collective comprised by student-artists. Seeking to relate the process of creating zines (MAGALHÃES, 1993) to the experiences in the city of Limoeiro do Norte, six moments of creation are presented. They took place in the public space and at the Colégio Diocesano and resulted in the production of five zines, in addition to the composition of a reading box and interventions in a display case. The actions in the city, mainly in the squares and their surroundings, are understood as a stage in the process of creating zines, which expands when it incorporates the participation of people and the representation of city spaces. Thus, this combination aims to bring the activities of the Creation and Arts Group closer to artistic experimentation. This perspective led the processes developed to frontier territories of art in which, starting from zines, opens dialogues with performance (COHEN, 2002), with the game (HUIZINGA, 2005), with drawing and sequential art (McCLOUD, 2008), with the artist's book (DERDYK, 2013), and also with the artisanal magazines produced in the city of Limoeiro do Norte between the 70s and 90s. The meetings, actions, processes and productions described were held between the months of August and December of 2019. During this period, the creation of author characters and the re-reading of illustrations by Revista de Cultura Kuandu (1977) are among the activities of the Creation and Arts Group. The compostion of reading boxes at the Dr. João Eduardo Neto Municipal Public Library; the design of passers-by in the Matriz square and the creation of a data-matrix; the conversation with living flowers in the square Nossa Senhora da Assunção and the incorporation of serigraphy into the zines printing process; a picnic in the Maria José de Freitas square, where it was possible to design the space of the square and think about the free interleaving of pages in the zines; and, finally, exchange and intervention using a display case in José Jerônimo square. Based on these actions, this research seeks to show a zine-city through the actions and processes of creation in the city of Limoeiro do Norte.